2022
DOI: 10.3390/ma15134398
|View full text |Cite
|
Sign up to set email alerts
|

Remineralization Efficacy of Four Remineralizing Agents on Artificial Enamel Lesions: SEM-EDS Investigation

Abstract: Dental remineralization represents the process of depositing calcium and phosphate ions into crystal voids in demineralized enamel, producing net mineral gain and preventing early enamel lesions progression. The aim of the present study was to qualitatively and quantitatively compare the remineralizing effectiveness of four commercially available agents on enamel artificial lesions using Scanning Electron Microscopy (SEM) combined with Energy Dispersive Spectroscopy (EDS) techniques. Thirty-six extracted third… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 50 publications
1
14
0
2
Order By: Relevance
“…Indeed, Balakrishnan et al evaluated the remineralization potential of various toothpastes over a period of 30 days and concluded that the extent of remineralization achieved was dose-dependent and increased with increasing the time of exposure and duration of the study [ 49 ]. In fact, our previous study, which evaluated the efficacy of these RA, showed that, after 7 days of treatment, a complete remineralization was not obtained; instead, only an initial reorganization of the enamel structure was observed [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, Balakrishnan et al evaluated the remineralization potential of various toothpastes over a period of 30 days and concluded that the extent of remineralization achieved was dose-dependent and increased with increasing the time of exposure and duration of the study [ 49 ]. In fact, our previous study, which evaluated the efficacy of these RA, showed that, after 7 days of treatment, a complete remineralization was not obtained; instead, only an initial reorganization of the enamel structure was observed [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The study was conducted at the Department of Clinical Sciences and Stomatology of Università Politecnica delle Marche (Ancona, Italy). Thirty-six human third molars extracted for orthodontic and periodontal reasons were collected [ 29 ]. All patients were informed in advance that their extracted teeth would be used for scientific purposes, and written consent was obtained before the experiment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, although there is evidence that these fluoride products reduce erosive and abrasive wear, it is essential to control the causal factors to prevent the progression of lesions [6]. However, the initial enamel demineralization surface may be treated with topical use of remineralizing agents containing fluoride, calcium and phosphate ions, achieving almost complete remineralization of the surface and a reorganization of the prismatic structure of the enamel [7], avoiding surface loss in the continuous demineralization-remineralization process.…”
Section: Introductionmentioning
confidence: 99%
“…enamel demineralization surface may be treated with topical use of remineralizing agents containing fluoride, calcium, and phosphate ions, achieving almost complete remineralization of the surface and a reorganization of the prismatic structure of the enamel [7], avoiding surface loss in the continuous demineralization-remineralization process.…”
mentioning
confidence: 99%